2012
DOI: 10.1093/humrep/der462
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian endometrioma: severe pelvic pain is associated with deeply infiltrating endometriosis

Abstract: In case of OMA, severe pelvic pain is significantly associated with deeply infiltrating lesions. In this situation, the practitioner should perform an appropriate preoperative imaging work-up in order to evaluate the existence of associated deep nodules and inform the patient in order to plan the surgical intervention strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 52 publications
1
65
0
13
Order By: Relevance
“…Although the parasympathetic system might be implicated as well, 27 other authors have observed a similar distribution of DIE. 14,15,52 EM is heterogeneously hyperintense on T1-weighted MRI due to blood collections and hypointense from hemosiderin depositions. On T2-weighted MRI, it has a similar heterogeneous appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the parasympathetic system might be implicated as well, 27 other authors have observed a similar distribution of DIE. 14,15,52 EM is heterogeneously hyperintense on T1-weighted MRI due to blood collections and hypointense from hemosiderin depositions. On T2-weighted MRI, it has a similar heterogeneous appearance.…”
Section: Discussionmentioning
confidence: 99%
“…In one study focusing exclusively on patients with rectosigmoid lesions, 48% and 84% had ovarian endometriosis and retrocervical lesions, respectively [17] (Figure 3). Both superficial peritoneal and ovarian endometriomas may be found in association with DIE in variable percentages, thus contributing to the intensity of painful stimuli, as well as to infertility [18]. Thisraises the question of whether DIE is an independent form of the disease, or whether it represents its most severe clinical representation [19].…”
Section: Discussionmentioning
confidence: 99%
“…A grande limitação desta pesquisa é que se trata de uma amostra com viés, pois 84,6% de todas as pacientes operadas em decorrência de dor pélvica crônica eram portadoras de EPI (o esperado seria algo em torno de 33% 19 ). No entanto, mesmo com essa amostra tendenciosa, houve diferença significativa em vários parâmetros avaliados quando se comparou o grupo de pacientes com Ca-125 normal (<35 U/mL) e aumentado (≥35 U/mL).…”
Section: Discussionunclassified